FLORISTIC, STRUCTURAL AND WOOD DENSITY CHARACTERS OF TREE COMMUNITY IN INTERIOR AND EDGE FOREST OF MOUNT PAPANDAYAN, WEST JAVA - Fatmawati Tihurua, Eka
Forest fragmentation is the main cause of patch formation. Gradient of abiotic and biotic characteristics from the exterior into the interior of forest fragment could lead to the formation distinct characteristics between forests located in the interior and edge of forest patch. Research on the characteristics of interior and edge forest is important to obtain understanding on the effect of fragmentation. The objectives of this study were to analyze the condition of interior and edge forest in Mount Papandayan based on floristic, structural and wood density of tree communities; to determine whether tree branch wood density can be used to estimate stem wood density of tree communities in Mount Papandayan. Vegetation analysis was conducted by establishing three plots of 20 x 50 m2 each in the interior and edge forest of Mount Papandayan. Each plot was divided into 10 x 10 m2 sub plots. All trees with diameter 10 cm or more at breast height were enumerated and measured. Branch samples with 1 - 2 cm diameter and 2 - 5 cm length were collected for measuring the wood density. Wood density measured from branch were compared to stem wood density obtained from World Agroforestry Database (ICRAF) and other references. This research found 29 species belonging to 26 genera and 20 families. Value of floristic, structural and wood density characters of interior forests were higher than those of the edge forests. The average of species richness of the interior forests was 13 species, which was greater than that the edge forests (10 species). The species diversity of the interior forests was higher than that of edge forests as indicated by the average of Shannon-Wiener diversity index of 2,2 ± 0,11 for the interior forests and 1,7 ± 0,39 for the edge forests. The averages of stem density were 716,67/ha and 463,33/ha for interior and edge forests, respectively. The interior forests had higher regeneration potential than the edge forests as indicated by larger number of small diameter trees in the interior than in the edge forests. The total basal area ranges were 17,78 - 52,23 m2/ha. The values of basal area in the interior forests (42,83 m2/ha) was higher than in the edge forests (31,44 m2/ha). This study found that percentages of species having low, moderate and high stem wood density were 37,93%, 51,72% and 10,34%, respectively. The average of stem wood density in the interior forests (0,63 g/cm3) was higher than in the edge forests (0,55 g/cm3). The interior forests had higher carbon storage potential than the edge forest as indicated by greater biomass of the interior forests (338,08 Mg/ha) than that of the edge forests (255,66 Mg/ha). Based on the species diversity and wood density characteristics, this study suggests that Mount Papandayan has been exposed to moderate level of disturbance. Moderate disturbance, adopting intermediate disturbance hypothesis, was indicated by the high diversity index. Based on the variation of wood densities among tree species, moderate disturbance is indicated by the presence of species with low, moderate and high wood density. The regression analysis between branch and stem wood density showed a determination coefficient of 0,28 (p value < 0,001) and this indicated that branch wood density could potentially be used to stem wood density, especially for tree communities in Mount Papandayan.